ANALYSIS OF COMBINED FOOTINGS ON EXTENSIBLE GEOSYNTHETIC-STONE COLUMN IMPROVED GROUND - Maheshwari, Priti (Journal of Civil Engineering, Science and Technology, 2017)
Analysis of combined footings resting on an extensible geosynthetic reinforced granular bed on stone column improved ground has been carried out in the present work. Various components of soil-foundation system have been idealized using lumped parameter modeling approach as: combined footing as finite length beam, granular layer as nonlinear Pasternak shear layer, geosynthetic reinforcement as elastic extensible membrane, stone columns as nonlinear Winkler springs and foundation soil as nonlinear Kelvin body. Hyperbolic constitutive relationships have been adopted to represent the nonlinear behavior of various elements of a soil-foundation system. Finite difference method has been employed to solve developed governing differential equations with the help of appropriate boundary and continuity conditions. A detailed parametric study has been conducted to study the effect of model parameters like applied load, flexural rigidity of footing, configuration of stone columns, ultimate bearing resistance of foundation soil and stone columns, tensile stiffness of geosynthetics and degree of consolidation on response of soil-foundation system by means of deflection and bending moment in the footing and mobilized tension in geosynthetic layer. These parameters have been found to have significant influence on the response of footing and the geosynthetic reinforcement layer. To quantify this, results have been nondimensionalized to produce design charts for ready use for the analysis of combined footings resting on such a soilfoundation system.